Divisão do trabalho inovador: análise do papel do Estado na perspectiva dos organismos de apoio de Birigui-SP - Cerizza, Andréia de Alcântara [UNESP] (2015)
The thesis' main objective was to analyse how the location, through their support and governance organisms, defines innovation, its realization in productive sectors and the difficulties to promote it and glimpses and appropriates the State's innovation policies, from existing institutional interactions in the territory. Among the specific objectives, it sought: (a) to develop a study on innovation and institutional interactions; (b) to list the major public policy innovation in Brazil between 2004 and 2014and the existing financial, technical and managerial support instruments; (c) to describe about the formation of the footwear's local productive arrangement -Birigui's LPA; (d) to list the support organisms in the footwear sector (LPA), and other productive sectors from Birigui -SP; (e) to analyze how the support and governance organisms perceive innovation, the State's action in the public innovation policies matter and the existence of interaction between the local and federal institutionalities. It was adopted as hypothesis the idea that the location, through their support organisms, does not have a consistent relationship with the federal institutionalities that promote and support innovation, in a systemic perspective, because the lack of efficient and effective communication between the State and the local in order to actualize innovation policies in the locality.